2019
DOI: 10.1080/01629778.2019.1590433
|View full text |Cite
|
Sign up to set email alerts
|

Latvian CDI: methodology, developmental trends, and cross-linguistic comparison

Abstract: In this article we report the results of a large-scale population study based on the Latvian adaptation of Communicative Development Inventories (CDI, Fenson et al. 2007)a parental report tool aimed at mapping the lexical and grammatical development of children under the age of three. Two CDI forms are discussed: CDI I: "Words and Gestures" (8-16 months), and CDI II: "Words and Sentences" (17-36 months). This article discusses the internet-based methodology used for the data collection, reports the main develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Data from the MB-CDI:WS are available from more than 41,000 children at Wordbank (http://wordbank.stanford.edu/) and are accessible through the R package wordbankr (Braginsky et al, 2020). This database (Frank et al, 2017) includes samples from 26 languages: Cantonese (Tardif et al, 2009), Croatian (Kovacevic et al, 1996), Czech (Markova & Smolík, 2013), Danish (Bleses et al, 2008), English (American; Fenson et al, 2007; Thal et al, 2013), English (Australian; Kalashnikova et al, 2016), French (French; Von Holzen et al, 2018), French (Quebecois; Trudeau & Sutton, 2011), German (Szagun et al, 2009), Greek (Cypriot; Taxitari et al, 2015), Hebrew (Hila Gendler Shalev, Tel Aviv University), Italian (Caselli et al, 1995), Kigiriama (Alcock et al, 2015), Kiswhahili (Alcock et al, 2015), Korean (Pae & Kwak, 2011), Latvian (Urek et al, 2019), Mandarin (Beijing; Liu & Chen, 2015; Tardif et al, 2009), Mandarin (Taiwanese; Liu & Chen, 2015), Norwegian (Simonsen et al, 2013), Portuguese (European; Irene Cadime, University of Minho); Russian (Eliseeva & Vershinina, 2009), Slovak (Svetlana Kapalková, Comenius University), Spanish (European; López Ornat et al, 2005), Spanish (Mexican; Jackson-Maldonado et al, 2003), Swedish (Eriksson & Berglund, 2002), and Turkish (Acarlar et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Data from the MB-CDI:WS are available from more than 41,000 children at Wordbank (http://wordbank.stanford.edu/) and are accessible through the R package wordbankr (Braginsky et al, 2020). This database (Frank et al, 2017) includes samples from 26 languages: Cantonese (Tardif et al, 2009), Croatian (Kovacevic et al, 1996), Czech (Markova & Smolík, 2013), Danish (Bleses et al, 2008), English (American; Fenson et al, 2007; Thal et al, 2013), English (Australian; Kalashnikova et al, 2016), French (French; Von Holzen et al, 2018), French (Quebecois; Trudeau & Sutton, 2011), German (Szagun et al, 2009), Greek (Cypriot; Taxitari et al, 2015), Hebrew (Hila Gendler Shalev, Tel Aviv University), Italian (Caselli et al, 1995), Kigiriama (Alcock et al, 2015), Kiswhahili (Alcock et al, 2015), Korean (Pae & Kwak, 2011), Latvian (Urek et al, 2019), Mandarin (Beijing; Liu & Chen, 2015; Tardif et al, 2009), Mandarin (Taiwanese; Liu & Chen, 2015), Norwegian (Simonsen et al, 2013), Portuguese (European; Irene Cadime, University of Minho); Russian (Eliseeva & Vershinina, 2009), Slovak (Svetlana Kapalková, Comenius University), Spanish (European; López Ornat et al, 2005), Spanish (Mexican; Jackson-Maldonado et al, 2003), Swedish (Eriksson & Berglund, 2002), and Turkish (Acarlar et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…However, involving parents in developing or validating assessment tools carries risks. For instance, the Latvian language adaptation of the MacArthur-Bates Communicative Development Inventories for children aged 8-16 and 16-36 months encountered low parental response rates (8%), attributed to outreach challenges and unequal distribution of parental education levels (Urek et al, 2019). Prior research by Vulane et al indicated that parents' assessments could be overly optimistic or pessimistic, or even superficial, impacting the accuracy of the information provided (Vulane, Taurina, Zirina, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%